2022
DOI: 10.3390/ma15238543
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Sensitized AISI 304 Stainless Steel in Acid Chloride Solution

Abstract: Corrosion resistance of sensitized austenitic stainless steel (SS) in chloride environments is currently the subject of numerous studies. Most of them are focused on neutral chloride solutions at room temperature and the experiments are carried out on ground stainless steels surfaces. This paper deals with the corrosion behavior of sensitized AISI 304 stainless steel in acid 1 M chloride solution (pH = 1.1) at the temperatures of 20 ± 3 °C and 50 °C. The specimens after sensitization are tested as covered by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The results of three independent corrosion tests consistently confirmed a significant increase in corrosion resistance after two doses of PIII nitriding [11]. Study [12] deals with the corrosion behavior of sensitized AISI 304 stainless steels in acid 1 M chloride solution (pH = 1.1) at temperatures of 20 ± 3 • C and 50 • C. The specimens after sensitization were tested as covered by high-temperature surface oxides, and after their chemical removal. The results obtained showed that sensitization significantly conditions corrosion regardless of the removal of high-temperature oxides, and the elevated temperature mainly acts as its accelerating factor.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The results of three independent corrosion tests consistently confirmed a significant increase in corrosion resistance after two doses of PIII nitriding [11]. Study [12] deals with the corrosion behavior of sensitized AISI 304 stainless steels in acid 1 M chloride solution (pH = 1.1) at temperatures of 20 ± 3 • C and 50 • C. The specimens after sensitization were tested as covered by high-temperature surface oxides, and after their chemical removal. The results obtained showed that sensitization significantly conditions corrosion regardless of the removal of high-temperature oxides, and the elevated temperature mainly acts as its accelerating factor.…”
mentioning
confidence: 74%
“…The work presented in this Special Issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] demonstrates the possibilities of further improving the microstructure quality and mechanical properties of metal alloys.…”
mentioning
confidence: 93%
“…In contrast, stainless steel, endowed with these protective elements, naturally becomes more susceptible to aggressive corrosive agents like PTA [39]. However, some austenitic stainless steels like 304 and 316 can be prone to PTA corrosion due to their higher nickel content and potential sensitization along grain boundaries [40]. Nickel alloys contain a significant amount of nickel, which provides excellent corrosion resistance in a wide range of harsh and corrosive environments.…”
Section: Pta Corrosion In Refineymentioning
confidence: 99%
“…The corrosion resistance of sensitized stainless steel has been analyzed under a chloride solution. As per the results obtained through multiple tests, it has been concluded that sensitization has significantly conditioned the corrosion resistance properties of the steel and too the high temperature has accelerated this process [14]. In a work, the rolling impact at room temperature on mechanical properties and microstructure of nitrogen-bearing AISI 304 austenitic steel has been analyzed.…”
Section: Introductionmentioning
confidence: 96%